PENGARUH GADGET TERHADAP PERKEMBANGAN SOSIAL ANAK DI TK AISYIYAH BUSTANUL ATHFAL VI - Sinta, Sinta; Ali, Muhamad; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by the use of gadget applications that can affect the social development of children. Based on the data that researchers obtained from kindergarten Aiyiyah Busthanul Athafal VI children who are at school kindergarten 69% of children who use gadgets applications. Therefore, researchers want to see whether the use of gadget applications affect the social development of children. The problem in this study is "How is the influence of application of gadgets to social development of children aged 4-6 years Aisiyiyah Busthanul Athfal VI type of Pontianak Southeast?". This study aims to obtain accurate information about the influence of application of gadgets to social children aged 4-6 years Aisyiyah Busthanul Athfal VI kindergarten Pontianak Southeast. This research uses quantitative approach and the method used is descriptive method. The form of research in this study is correlational cause-effect. Research subjects in this study were 24 children and the respondents were teachers. Data collection techniques used were questionnaires and interviews. While the technique used to analyze the data is descriptive and statistical analysis by looking at the average and regression kolerasi. Based on Regression Coleration test, obtained Fcount of 0.674 and obtained Ftabel of 4.26. Thus, Fhitung ≤ Ftable (0.674 ≤ 4.26) then HO iterima and Ha rejected, meaning there is no effect on the use of gadget applications on social development of children aged 4-6 years in kindergarten Aisyiyah Busthanul Athfal VI.Keywords :Use of gadget apps, social development